Functional response and life history parameters of Apanteles taragamae, a larval parasitoid of Maruca vitrata - Dannou, E.A.; Tamo, Manuele; Huis, A. van; Dicke, M. (Springer, 2010)
The legume pod borer Maruca vitrata Fabricius (Lepidoptera: Crambidae) is a serious pest of cowpea in West-Africa. The parasitoid Apanteles taragamae Viereck (Hymenoptera: Braconidae) that originates from Taiwan is a potential candidate for biological control of M. vitrata. We investigated under laboratory conditions the functional response of the parasitoid by offering each experienced female 10, 20, 30 and 40 larvae of M. vitrata. We studied the influence of different host larval ages on the development, longevity, sex ratio, lifetime fecundity and parasitization rate of the wasp. In a comparative study, we also investigated the life history of A. taragamae and M. vitrata at different temperatures in the range of 20–30°C. The parasitoid successfully parasitized two- and three-day-old host larvae (first and second instars). Younger larvae (one-day-old) were parasitized to a lesser extent, and only males developed in them. Older larvae were not parasitized, partly because of defensive host behaviour. The success of parasitization was positively correlated with the density of two-day-old M. vitrata larvae. Parasitoid developmental time and longevity decreased with increasing temperature. The intrinsic rate of population increase (rm) exhibited an optimum curve with a maximum at 24–28°C. For the host M. vitrata, rm was maximal at temperatures of 26–30°C. The data are discussed in the context of the potential of A. taragamae for biological control of M. vitrata.